1990
DOI: 10.1111/j.1939-1676.1990.tb00875.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic-Plasmacytic Enteritis in 24 Dogs

Abstract: Lymphocytic-plasmacytic enteritis (LPE) was dia nosed by intestinal biopsy in 24 dogs with chronic tions were not documented, although four patients were German Shepherd dogs. Hypoproteinemia, hypoalbuminemia, and hypoglobulinemia were common and most likely a result of protein-losing enteropathy. Other biochemical abnormalities were uncommon. Intestinal malabsorption was common. Neutrophilia (sometimes with increased band neutrophils), monocytosis, lymphopenia, and eosinopenia were the most consistent hematol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 8 publications
4
23
1
Order By: Relevance
“…In a previous study on Shiba dogs with CE, the median age was 4.9 years [6], which was almost comparable to the ages reported in other retrospective studies of dogs with IBD and CE [10-12]. Similarly, in our study, the median age of the Ls group was 5 years (mean 5.2).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In a previous study on Shiba dogs with CE, the median age was 4.9 years [6], which was almost comparable to the ages reported in other retrospective studies of dogs with IBD and CE [10-12]. Similarly, in our study, the median age of the Ls group was 5 years (mean 5.2).…”
Section: Discussionsupporting
confidence: 89%
“…In a previous study on Shiba dogs, the median survival was 74 days, and the survival rates at 6 months and 1 year were 46% and 31%, respectively [6]. In the other reports on dogs with IBD and LPE, which included several breeds, the survival rates at 6 months were 96% and 74%, respectively [8,12]. Compared to these reports, our findings strongly suggest a poor outcome for Shiba dogs with CE.…”
Section: Discussionsupporting
confidence: 43%
“…Previous studies reported a higher prevalence of hypoproteniemia in these LPE dogs compared to our study, ranging from 24~63% [3,13,14,21]. It is unclear why the LPE dogs in the present study had a lower prevalence of hypoproteinemia compared to previous studies.…”
Section: Discussioncontrasting
confidence: 83%
“…Canine enteropathies may be multifocal in distribution, 1–3 which favors collecting biopsy samples from more than 1 anatomical location. Taking samples of ileal mucosa, however, is not a routine procedure.…”
mentioning
confidence: 99%